ANALISIS PROSES PERENCANAAN DAN PENGANGGARAN BELANJA MODAL DPU KOTA SEMARANG TAHUN ANGGARAN 2019 - Muji Bagus Prastyo; Antonius; Abdul Rochim (Jurnal Teknik Sipil dan Arsitektur, 2024)
Presidential Regulation No. 54 of 2010 concerning Government Procurement of Goods/Services which is relatively more comprehensive is expected to be able to regulate order in the implementation of government procurement of goods and services. The government provides the widest opportunity for small businesses, micro-enterprises and cooperatives to take part in tenders for goods/services procurement work packages. The purpose of this study is divided into 2 (two) which are research stages, namely analyzing the effectiveness of the regional financial performance of the Semarang City Government, analyzing the efficiency of the regional financial performance of the Semarang City Government with variables. The type of research used in this research is research using quantitative methods with SWOT analysis and questionnaire methods, qualitative descriptive analysis by measuring the financial performance of the DPU Semarang City Government through the concepts of effectiveness and efficiency. Measurement is measured through a comparison of actual revenue with revenue budget Based on the results of the analysis using SWOT analysis with IFAS and EFAS scores, it can be seen that the Planning and Budgeting of Capital Expenditures for the DPU for the City of Semarang for the 2019 Fiscal Year is located in Quadrant I. From the calculation of the effectiveness and efficiency of the DPU for the City of Semarang in 2019 it looks effective but not efficient, because it obtained the effectiveness value is 105.53% where the value indicates it is effective, and the efficiency value is 106.7% where the value indicates it is not efficient.